Kinerja Keuangan Dilihat Dari Prespektif Corporate Governance dan Ukuran Pada Perusahaan Perbankan - Anisya Sri Septika; Muhammad Rivandi (ITScience (Information Technology and Science), 2023)
Financial performance is a financial report that shows the condition of the company which will be used as consideration for the company to take further action and for the public to assess the smooth running of the company. The aim of this research is to determine the influence of the Board of Directors, Audit Committee and Banking Company Size on the Financial Performance listed on the BEI. The analytical method used by researchers is the logistic analysis method with a purposive sampling technique and the data used is annual report data and financial reports of manufacturing companies in the basic materials, industrials, non-consumer subsectors listed on the Indonesian Stock Exchange (BEI) for the 2019 -2021 period. Based on the hypothesis test, the research results show that the Board of Directors and Company Size have no effect on Banking Financial Performance, while the Audit Committee has a positive and significant effect on Banking Financial Performance. Keywords: Board of Directors, Audit Committee, Company Size and Financial Performance